Treatment of non-carious cervical lesions with the de-epithelialized free gingival graft and coronal advancement flap method: Penanganan lesi servikal non karies dengan metode de-epithelialized free gingival graft dan coronal advancement flap - Daniel Tetan-El; Hasanuddin Thahir; Jennifer Tjokro (Makassar Dental Journal, 2024)
Gingival recession is the most common aesthetic problem related to periodontal tissues, especially when it occurs in the maxilla-ry anterior teeth. A 44-year-old man complained of receding gums that made it difficult to brush his teeth. In teeth 11-17, 21-27, 31, 32, 42-45 Miller Class III 2-3 mm gingival recession and type 2 non-carious cervical lesions. The gingival phenotype was mo-derate in size. The patient was referred to the Periodontics Department for perioesthetic treatment of de-epithelialised free gingi-val graft and coronal advancement flap. After prosthodontic treatment for the back teeth, a combination treatment of DFGG and modified envelope CAF was performed with a combination of full and partial thickness flaps. After 2 weeks, the healing process was found to be favourable aesthetically and functionally. The periodontal state was normal and the root coverage area was fa-vourable. It was concluded that gingival recession treated with de-epithelialised gingival graft combined with coronal advance-ment flap gave the best aesthetic and functional results. Gingival recession is the most common aesthetic problem related to periodontal tissues, especially when it occurs in the maxilla-ry anterior teeth. A 44-year-old man complained of receding gums that made it difficult to brush his teeth. In teeth 11-17, 21-27, 31, 32, 42-45 Miller Class III 2-3 mm gingival recession and type 2 non-carious cervical lesions. The gingival phenotype was mo-derate in size. The patient was referred to the Periodontics Department for perioesthetic treatment of de-epithelialised free gingi-val graft and coronal advancement flap. After prosthodontic treatment for the back teeth, a combination treatment of DFGG and modified envelope CAF was performed with a combination of full and partial thickness flaps. After 2 weeks, the healing process was found to be favourable aesthetically and functionally. The periodontal state was normal and the root coverage area was fa-vourable. It was concluded that gingival recession treated with de-epithelialised gingival graft combined with coronal advance-ment flap gave the best aesthetic and functional results.